Peran Supervisi Manajerial Dalam Meningkatkan Efektivitas Proses Pembelajaran - Assyifa Wahidatul Sholeha; Dhea Tamara; Dian Irdasari; Subandi Subandi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Abstract. This study aims to explore the role of managerial supervision in improving the effectiveness of the learning process in educational institutions. Managerial supervision, as part of school management, plays an important role in monitoring, evaluating, and providing support for improving the quality of learning. Through a qualitative approach, this study conducted an in-depth literature review of various related studies to analyze how the role of managerial supervision contributes to the quality of teaching, teacher motivation, and student academic achievement. The results of the study indicate that effective managerial supervision is able to create a conducive working environment for teachers, improve professional competence, and encourage innovation in teaching strategies. Supervision that is carried out in a planned and sustainable manner has been proven to have a positive impact on improving the quality of learning. The conclusion of this study shows that managerial supervision has a significant contribution in realizing an effective and quality learning process. Keywords: Managerial Supervision, Effectiveness, Learning Process